2017
DOI: 10.1007/s10661-017-6223-9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations in diploid and triploid oysters (Crassostrea gigas) from three farms on the north-central coast of Sinaloa, Mexico

Abstract: The concentrations of Cu, Cd, Pb, Zn, and Hg in diploid and triploid oysters from three farms (Guasave, Ahome, and Navolato) on the north-central coast of Sinaloa, Mexico, were assessed based on samples recovered during a single culture cycle 2013-2014. Metal burdens were more strongly correlated (p < 0.05) with the location of the farm than with either the ploidy or the interaction of both variables. The metal concentration ranking for oysters of both ploidies from the three farms was Zn > Cu > Cd > Pb > Hg. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
8
2
3
Order By: Relevance
“…The Ni values of the edible tissue of Sphoeroides spp. were higher to those reported in recent studies on other marine species of the region [35, 47,67,80,81]. However, the concentration of Ni in predatory shes has been reported to be slightly higher than those in herbivorous and omnivorous species [79].…”
Section: Resultscontrasting
confidence: 66%
“…The Ni values of the edible tissue of Sphoeroides spp. were higher to those reported in recent studies on other marine species of the region [35, 47,67,80,81]. However, the concentration of Ni in predatory shes has been reported to be slightly higher than those in herbivorous and omnivorous species [79].…”
Section: Resultscontrasting
confidence: 66%
“…The difference of metal concentration between triploid and diploid oysters (somatic tissue) was not significant either. Amiard et al () and Sevilla et al () also found metal bioaccumulation patterns and metal concentrations to be similar for both ploidies, and the major factor governing metal accumulation by oysters was influenced by the levels of metal in the water. Considering that triploid oysters do not have reproduction throughout the year, this further indicated that gonadal development did not affect metal accumulation in somatic tissue.…”
Section: Discussionmentioning
confidence: 87%
“…capax de la zona de muestreo. Específicamente, en la costa este de Baja California Sur, se desarrollan diversas actividades antropogénicas (urbanización, turismo, pesquería y minería, Romero-Gil, 1991) distintas a las que se realizan a lo largo de la costa este del Golfo de California, donde predomina la agricultura intensiva, acuacultura y manufactura, entre otras (Frías-Espericueta et al, 2011;Muñoz-Sevilla et al, 2017) y cuyos efectos en algunas especies de moluscos han sido reportados. Por ejemplo, Yee-Duarte et al (2017, 2018 revelaron desórdenes fisiológicos reproductivos en la almeja chocolata M. squalida asociados a compuestos tóxicos en la zona de nuestro muestreo.…”
Section: Megapitaria Squalidaunclassified